Soil testing, soil stability and ground improvement : proceedings of the 1st GeoMEast International Congress and Exhibition, Egypt 2017 on sustainable civil infrastructures /: proceedings of the 1st GeoMEast International Congress and Exhibition, Egypt 2017 on sustainable civil infrastructures. ([2018]) - Unknown
No abstract available